A low sensitivity energetic cocrystal of ammonium pentazolate. Issue 1 (2nd January 2023) - Xu, Yuangang; Li, Dongxue; Wang, Pengcheng; Lin, Qiuhan; Ding, Lujia; Hou, Tianyang; Yuan, Yuan; Lu, Ming
ABSTRACT: A new cyclo -pentazolate anion-based energetic cocrystal NH4 N5  · 1/6NH4 Cl was synthesized. The structure, thermal behavior, sensitivity, and detonation properties of NH4 N5  · 1/6NH4 Cl were studied. Cube-shaped NH4 N5  · 1/6NH4 Cl crystallizes in the F d-3 m space group, and is formed by hydrogen bonding interactions. DSC-TG-MS combined techniques show that NH4 N5  · 1/6NH4 Cl has better thermal stability than NH4 N5 . The cocrystal exhibits low impact and friction sensitivity, and largely reduces the mechanical sensitivity of NH4 N5 . Furthermore, the cocrystal is predicted to have a detonation velocity of about 8.3 km s −1 and a detonation pressure of about 21.4 GPa, respectively, indicating excellent detonation performance.